Respuestas

¡La mejor respuesta!
2012-06-22T01:47:13+02:00

a) x^2 -5x+6=0

 

entonces:

 

   x^2 -5x +6

    x          -3

    x          -2   

 

x-3=0      x-2=0

x=3         x=2


b)x^2+x+1=0


entonces:


a=1

b=1

c=1


formula general:


raiz 1 : -b+(b^2-4ac)^(1/2)    raiz 2:  -b-(b^2-4ac)^(1/2)

                       2a                                          2a 


raiz 1 : -(1)+((1)^2-4(1)(1))^(1/2)    raiz 2:  -(1)-((1)^2-4(1)(1))^(1/2)

                               2(1)                                                 2(1) 


raiz 1: -1+(-3)^(1/2)        raiz:  -1-(-3)^(1/2)

                    2                                   2  


c) 2x-3=1-2x+x^2

    x^2 -4x+4=0

 

entonces:

 

   x^2 -4x +4

    x          -2

    x          -2   

 

x-2=0      x-2=0

x=2         x=2

 

un gusto ......=D

2012-06-22T02:28:46+02:00

2x-3=1-2x+x^{2}

0=x^{2}-4x+4

 

en donde este ejercicio solo tiene una raiz que es 2